Factors determining the use of digital technologies and physical activity tools in the training of esports players - Shynkaruk , Oksana; Andrieiev , Arsenii (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. The rapid development of esports is accompanied by an increase in cognitive, sensorimotor, and psycho-emotional loads on players, which necessitates the improvement of their training systems. Modern training practice is largely based on the extensive use of digital technologies; however, the role of physical activity tools as compensatory and preventive components remains insufficiently systematized. Purpose of the study was to identify the factors determining the use of digital technologies and physical activity tools in the training of esports players and to substantiate the feasibility of their integrated application. Materials and methods. The study involved 15 experts (esports coaches, competitive performance analysts, and researchers in the field of physical culture and sport). The research methods included theoretical analysis, synthesis of scientific sources, analysis of training practice, and expert evaluation. Statistical processing was carried out using non-parametric methods (median, quartiles, Kendall’s coefficient of concordance). The study was conducted in accordance with ethical principles, and all participants provided informed consent. Results. It was established that digital technologies constitute a system-forming component of esports training and include training-game technologies, analytical and statistical platforms, psychophysiological monitoring tools, and organizational digital platforms. The highest expert significance was assigned to training-game technologies and analytical platforms (Me = 5.0; p < 0.01). Physical activity tools were found to have predominantly compensatory, preventive, and recovery-oriented functions, with corrective-preventive and recovery exercises identified as priorities (Me = 5.0; p < 0.01). The use of digital and physical activity tools was shown to be determined by the combined influence of cognitive, physiological, and organizational factors, among which cognitive and physiological determinants play a leading role. Conclusions. The combination of digital technologies with rationally selected physical activity tools forms an integrated system for esports player training aimed at enhancing gaming performance, maintaining functional condition, and preventing overload. The obtained results substantiate the feasibility of implementing an integrated training model for esports players that takes into account cognitive, physiological, and organizational determinants.